Salvation in the New Testament : perspectives on soteriology - Van der Watt, J. G. 1952- (Novum Testamentum, Supplements, 2005)
Salvation in the New Testament offers an analysis of the soteriological perspectives and language of the different books of the New Testament. Special attention is given to the imagery used in expressing soteriological ideas. Salvation deals with becoming part of the people of God. In Salvation in the New Testament special attention is given to the nature and power of the salvific language used in the New Testament to express the dynamics of salvation. Individual articles on the different books of the New Testament highlight the diverse perspectives offered in these documents. The emphasis especially falls on the different images and metaphors which were used to express the event and moment of salvation, rather than on the results (ethics or behaviour) of salvation. An overview of the different perspectives on soteriology in the New Testament offers the opportunity to compare similarities and differences in concepts and expressions. It also illustrates the dynamic interaction between historical situations and salvific language and expression.